Transverse Plane Tendon and Median Nerve Motion in the Carpal Tunnel: Ultrasound Comparison of Carpal Tunnel Syndrome Patients and Healthy Volunteers - van Doesburg, Margriet H. M. (Public Library of Science, 2012)
BACKGROUND: The median nerve and flexor tendons are known to translate transversely in the carpal tunnel. The purpose of this study was to investigate these motions in differential finger motion using ultrasound, and to compare them in healthy people and carpal tunnel syndrome patients. METHODS: Transverse ultrasounds clips were taken during fist, index finger, middle finger and thumb flexion in 29 healthy normal subjects and 29 CTS patients. Displacement in palmar-dorsal and radial-ulnar direction was calculated using Analyze software. Additionally, the distance between the median nerve and the tendons was calculated. RESULTS: We found a changed motion pattern of the median nerve in middle finger, index finger and thumb motion between normal subjects and CTS patients (p<0.05). Also, we found a changed motion direction in CTS patients of the FDS III tendon in fist and middle finger motion, and of the FDS II and flexor pollicis longus tendon in index finger and thumb motion, respectively (p<0.05). The distance between the median nerve and the FDS II or FPL tendon is significantly greater in patients than in healthy volunteers for index finger and thumb motion, respectively (p<0.05). CONCLUSION: Our results suggest a changed motion pattern of the median nerve and several tendons in carpal tunnel syndrome patients compared to normal subjects. Such motion patterns may be useful in distinguishing affected from unaffected individuals, and in studies of the pathomechanics of carpal tunnel syndrome.